Swallowing after transoral surgery for oropharyngeal cancer: comparison with primary chemoradiotherapy outcomes. Issue 2 (April 2017) - Dawe, Nicholas; O'Hara, James
Abstract : Purpose of review: Survival equipoise is recognized between the contemporary surgical and oncological approaches to oropharyngeal squamous cell carcinoma treatment. Primary transoral surgery (TOS) options have emerged that utilize either laser or robotic techniques. Our review presents an overview of the evidence available for swallowing outcomes following TOS approaches and compares these with outcomes following primary oncological management. Recent findings: Meta-analysis of swallow outcomes following TOS or (chemo)radiotherapy is not possible given the heterogeneity of the available data. There are suggestions of less swallowing impairment following primary TOS, but the favourable selection of patients to these case series must be considered. Summary: Minimizing swallowing impairment following oropharyngeal squamous cell carcinoma treatment, while ensuring oncological efficacy, should be a priority for head and neck healthcare providers. Primary TOS may offer an advantage to patients, but only through a team approach that considers how adjuvant oncological therapy could be tailored to individuals. High-quality clinical trials are in progress that will inform future practice.